SISTEM PAKAR UNTUK MENGIDENTIFIKASI KERUSAKAN PADA KENDARAAN RODA EMPAT (MOBIL BERBAHAN BAKAR BENSIN) - Dwi Mumpuni, Indah (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
Artificial Intelligence (AI) is now in full swing as the manufacture developed an expert system application. Expert system is a computer system that has the ability to make expert decisions, this expert system is a high degree of specialization that seek to duplicate the function of an expert or experts in a particular area of expertise, expert systems can also act as advisers or consultants in a given environment, so that even ordinary people can make the expert system as a tool to solve a problem or issue at hand. The purpose of this expert system design is to make the software checks the damage of four-wheeled vehicles. Results to be achieved in the design of this system is a software that can serve as an expert to determine the damage to four wheel drive vehicles. Keywords: Expert System, Checking Damage